Book Review Essay: “Conversion Disorder: Listening to the Body in Psychoanalysis” by Jamieson Webster - Ricky Varghese (EJP import test, 2020)
Conversion Disorder: Listening to the Body in Psychoanalysis Jamieson Webster (New York: Columbia University Press, 2018) 312 pp., £32.00 (hardcover), £32.00 (e-book)